The Role of Inclusive Leadership in Building a Condusive Organizational Climate at SD Negeri 2 Glapansari - Kulsum, Umi; Prihantari, Kristiana; Budi Rahayu, Esti; Nurkolis, Nurkolis (Jurnal Ragam Pengabdian, 2026)
A conducive organizational climate in schools is an important factor in improving collaboration, teacher motivation, and the effectiveness of educational management. This study aims to analyze the role of inclusive leadership in building a conducive organizational climate at SD Negeri 2 Glapansari. The research employed a qualitative descriptive approach to obtain an in-depth understanding of the principal’s inclusive leadership practices in creating a positive school organizational environment. The subjects of the study consisted of one principal, six teachers, one educational staff member, and two school committee members. Data were collected through observation, interviews, and documentation. The validity of the data was examined using source triangulation and technique triangulation, while data analysis applied the interactive model of Miles, Huberman, and Saldaña, including data reduction, data presentation, and conclusion drawing. The findings revealed that the principal’s inclusive leadership played a significant role in establishing a conducive organizational climate through open communication, teacher involvement in decision-making, strengthening collaboration among school members, appreciation of diversity, and the creation of a harmonious working environment. Teachers felt valued, motivated, and actively involved in school programs due to the democratic and participatory leadership approach implemented by the principal. Furthermore, the positive interpersonal relationships and collaborative culture among school members contributed to a comfortable and supportive working atmosphere. Therefore, inclusive leadership can be considered an effective leadership approach in fostering a positive organizational climate and improving the effectiveness of educational management in elementary schools.